The Urgency Of Transparency In State Officials' Spending To Reduce Corruption Rates In Indonesia - Desyi Erawati; Raihan Hanasi; Rizal Bakti; Muhammad Aiman; Apriani Riyanti (Yayasan Inovasi Kemajuan Intelektual, 2023)
Corruption remains a structural and endemic challenge that hampers economic development, undermines democratic institutions, and erodes public trust in Indonesia. Despite various legal and institutional reforms, the level of corruption, as measured by indices such as Transparency International's Corruption Perceptions Index (CPI), has not shown significant, sustained improvement. This study argues that one critical gap in the public accountability system is the lack of adequate, specific transparency in reporting the operational and discretionary expenditures of state officials, particularly at the executive and legislative levels. The purpose of this study is to analyze the theoretical and empirical urgency of implementing a comprehensive transparency regime for official expenditures (e.g., official travel, representation costs, and the use of tactical/operational funds) to prevent and detect corrupt practices early. Drawing on the Theory of Public Accountability and international experience (e.g., Freedom of Information Acts), this study uses a normative-empirical approach to identify a negative correlation between expenditure data disclosure and corruption incidents. The central hypothesis is that spending transparency creates a deterrent effect through heightened public scrutiny, thereby significantly reducing opportunities for misappropriation and strengthening officials' ethical commitment. This finding is crucial for formulating evidence-based anti-corruption policies in Indonesia, particularly regarding revisions to the Public Information Disclosure Law (KIP) and regulations on State Officials' Wealth Reports (LHKPN).